Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.21203/rs.3.rs-110077/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Statins in Patients with COVID-19: A Retrospective Cohort Study in Iranian COVID-19 Patients

Abstract: Background: The coronavirus disease 2019 (COVID-19) pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection has profoundly affected the lives of millions of people. To date, there is no approved vaccine or specific drug to prevent or treat COVID-19, while the infection is spreading at an alarming rate globally. Because the development of effective vaccines or novel drugs could take several months (if not years), repurposing existing drugs is considered a more efficient strateg… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 6 publications
2
13
0
Order By: Relevance
“…Patients consuming statins had more normal computed tomography (CT) scan results than others (OR = 0.41, 95% CI = (0.07–2.33), P = 0.312). However, none of these variables were statistically significant [20] . A single-center survey in California found that using statins significantly reduced the risk of severe COVID-19 (adjusted OR 0.29, 95 %CI 0.11 to 0.71, p < 0.01) and recovered faster in hospitalized patients without the severe form of the disease (adjusted HR for recovery 2.69, 95 %CI 1.36 to 5.33, p < 0.01) [21] .…”
Section: Discussionmentioning
confidence: 81%
“…Patients consuming statins had more normal computed tomography (CT) scan results than others (OR = 0.41, 95% CI = (0.07–2.33), P = 0.312). However, none of these variables were statistically significant [20] . A single-center survey in California found that using statins significantly reduced the risk of severe COVID-19 (adjusted OR 0.29, 95 %CI 0.11 to 0.71, p < 0.01) and recovered faster in hospitalized patients without the severe form of the disease (adjusted HR for recovery 2.69, 95 %CI 1.36 to 5.33, p < 0.01) [21] .…”
Section: Discussionmentioning
confidence: 81%
“…We further examined 26 full-text articles and searched the references of relevant articles, retrieving 2 additional publications. Finally, 22 studies met all inclusion criteria [ 1 , 9 , 10 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. The flow diagram of the systematic articles search is presented in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Armed with the capacity to utilize the suggested methods, we can aim for a robust immune system and fight this battle ( Mohamed and Rezaei, 2020 ), which has persisted for a year now ( Jabbari and Rezaei, 2020 ). Pro-sensing biomaterials are of emerging interest that can accelerate the early immune responses ( Saghazadeh and Rezaei, 2021 ), while testing the clinical efficacy of a variety of ancient and modern therapies that selectively modulate inflammation remains under investigation ( Pezeshki and Rezaei, 2021 ; Zarandi et al, 2021 ; Palit et al, 2020 ; Peymani et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%